Light and culture medium formulations for in vitro germination and development of Brassavola perrinii - Targanski Sajovic Pereira, Suzana (Revista Ciência Agronômica, 2021)
The improvement of in vitro propagation techniques using appropriate artifi cial light sources and culture mediumformulations is important to allow the mass production of individuals with high genetic variability. Thus, this research aimed tostudy the effect of light sources from fl uorescent lamps and light-emitting diodes (LEDs) and culture medium formulations onthe germination and initial development of the orchid species Brassavola perrinii. The experiment was set up in a completelyrandomized design in a 5 × 4 factorial scheme, consisting of fi ve light sources – fl uorescent lamp (100%), white LED (100%),blue LED (100%), red LED (100%), and blue LED (50%) + red LED (50%) – and four culture medium formulations – MS, ½ MS,VW, and K –, with four replications and a mean of 125 seeds per plot. The percentage of germination, chlorophyll protocorms, andprotocorm development through the classes P1, P2, P3, and P4 to calculate the protocorm development index were evaluated at 90days after sowing. The data were subjected to analysis of variance and the means were compared by the Tukey test (p < 0.05). Thepercentage of germination for B. perrinii was not infl uenced by light spectra but was higher in the ½ MS and VW formulations.The highest protocorm development index of B. perrinii was observed when the species was submitted to the light spectrum of thelighting source with fl uorescent lamps in the VW culture medium.